New dimensions in Nigerian Banking - Nwankwo, G. O. (1973)
The purpose of this talk is to examine the developments of new dimensions in Nigerian Banking and assess their impact on our economy.
Includes bibliographical footnotes
ahz 04/04/2019
Loans
Keywords: Banking services; Banking; Nigeria